The Effect of Sodium Silicate (Na2SiO3) Addition against Water Absorption and Compressive Strength in Bricks - Ridha, Abdi (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
This study investigates the impact of Sodium Silicate (Na₂SiO₃) addition on the water absorption and compressive strength of bricks, aiming to enhance understanding of material properties in construction. Sodium Silicate was incorporated into the brick mix at concentrations of 0%, 10%, 20%, and 30% by weight of cement, with a mix ratio of 1:7 (cement). The compressive strength and water absorption tests were conducted after a 28-day curing period, following the Indonesian National Standard (SNI) procedure 03-0349-1989. The results indicate that increasing Sodium Silicate concentration led to a decrease in compressive strength, with values of 45.62 MPa, 50.27 MPa, and 59.03 MPa observed at 10%, 20%, and 30% addition levels, respectively, compared to the control (standard bricks). Conversely, water absorption increased by 0.79%, 1.47%, and 2.31% at these respective concentrations. The observed reduction in compressive strength is attributed to the gel-like and adhesive properties of Sodium Silicate, which potentially hinder uniform water distribution within the brick matrix, thereby affecting the overall material performance. These findings suggest that while Sodium Silicate can enhance water resistance in bricks, its use at higher concentrations may compromise structural integrity. Further research is recommended to optimize the concentration of Sodium Silicate for balanced mechanical properties and durability in brick production.